Legal problems of the corruption prevention in state and municipal health care institutions - M. A. Anishchenko (Zaporozhye State Medical University, 2018)
The purpose of the research: to investigate the problems of legal regulation of the corruption prevention in health care institutions, outline ways of their solution. Materials and methods: normative-legal base of Ukraine, method of analysis, method of synthesis, comparative-legal method. Results: The issues of the corruption prevention, including its prevention in health care institutions, are regulated by a number of normative legal acts, in particular the Law of Ukraine "About Corruption Prevention", the Code of Ukraine on Administrative Offenses, and the Criminal Code of Ukraine. However, a number of norms are collisional, therefore they need legal improvement. Conclusions: One of the main problems of the corruption prevention is the formation of a unified normative approach to the legal regulation of the health care institutions financing, which is to bring in compliance all other normative legal acts regulating these issues with the Constitution of Ukraine or changing the Constitution. The requirements of the Criminal Code of Ukraine, the Labor Code of Ukraine, and the Civil Code of Ukraine require alignment with the Law of Ukraine "About Corruption Prevention". It is necessary to legislatively define mechanisms for the protection of the rights of officials, in particular the right to extract information about a person from the Unified State Register of persons who committed corruption or corruption-related offenses in the event of the expiration of the period provided for by the Code of Ukraine on Administrative Offenses and the Labor Code of Ukraine after the end of which the person is considered to be not attracted to a certain type of responsibility. The urgent need is to increase social standards for health workers. The need for significant improvement of the notion and settlement of the conflict of interests in accordance with the current legislation is dictated by the threat of bringing this legal institution to the point of absurdity. And, of course, strengthening legal education and legal work with patients and health care providers, maximizing the openness of information is an effective prevention of corruption manifestations.